Global Hydrogen Trade to Meet the 1.5°C Climate Goal Part III - Green Hydrogen Cost and Potential (International Renewable Energy Agency, 2022)
This report estimates the potential for green hydrogen production as a function of land availability, considering exclusion zones such as protected areas, forests, wetlands, urban centres, slope and water scarcity.